Motives of pro-environmental behavior in the context of changing level of Poles ecological awareness - Jolanta Zrałek (Polityki Europejskie, Finanse i Marketing)
The purpose of the present study was to identify and characterize the motives of selected pro-environmental consumer behaviors on the background of changes in the level of ecological awareness of Poles. Taking into account this goal the basic information derived from the field research conducted by the author – two surveys carried out in 2012 on unrepresentative samples of students of University of Economic in Katowice. Changes in the level of Poles environmental consciousness were based on information that originate from secondary sources – reports from nationwide researches conducted by specialized research agencies. This article concluded that environmentally friendly consumer behaviors are driven simultaneously by more than one motive. Even though the level of Poles environmental awareness is growing the ecological premises are not the main driving force of their pro-ecological behaviors.